Keterwakilan Perempuan Dalam Politik (Studi Kasus: Caleg Perempuan DPR RI Tahun 2024-2029) - Rambe, Reni Damayanti; Dompak, Timbul; Salsabila, Lubna (Jurnal Pemerintahan dan Politik, 2025)
This study analyzes women's representation in politics in the Indonesian House of Representatives in 2024-2029. Although women's participation in politics has increased, their number in parliament has still not reached the target of 30% according to Law Number 7 of 2017 concerning Elections. In the most recent election, women's representation reached 21.9%, up from the previous period, but still shows a gap between the number of female candidates nominated and those elected. Personal, cultural, and structural barriers are the main factors that hinder the achievement of gender quotas. Therefore, although affirmative action has been implemented, further efforts are still needed to encourage the role of women in politics.